Developing a Tool for Cross-Functional Collaboration: the Trajectory of an Annual Clock - Ruotsala, Riikka (Outlines. Critical Practice Studies, 2014)
This empirical study examines how practitioners from the organizational functions of human resources, occupational safety and occupational health services within a Finnish industrial organization view the challenges that production supervisors face in their daily work. The article presents a formative intervention, which focuses on supervisors’ changing work and how these organizational support functions could collaboratively serve supervisors better, especially in their task of promoting well-being at work. The article approaches this collective learning effort from the framework of the Cultural Historical Activity Theory (CHAT), by examining how crossfunctional collaboration evolves and the transitions through which it develops in an intervention process. The development of collaboration is analysed through a process of collective concept and tool formation by following a cross-meeting trajectory of specific annual clock episodes. An annual clock, a co-ordinating tool used in organizations to assist the yearly planning and management of specific operations, emerged in the intervention as the practitioners’ attempt to synchronize overlapping and inconsistent well-being related practices assigned to supervisors. The article presents a framework that can be applied in this kind of combined empirical analysis of tool development and the evolving collaboration. The analysis shows how the idea of the annual clock grew through multifaceted conceptualizations, in which it first had the status of a conceptual object, then a collaborative tool, and eventually a script for becoming a novel cross-functional practice. Simultaneously, the mode of interaction expanded from a function-based co-ordination to task-oriented co-operation, and finally to communication.